The Effect of Oatbits Biscuits (Oat 8 Choco Hazel) and SGM Bunda Milk on Weight Gain in First-Trimester Pregnant Women with Chronic Energy Deficiency at the Public Maternity Hospital in Bogor in 2024 - Riska Meca Dwikusrini; Putri Agus Febriyani; Meinasari Kurnia Dewi (Dharmawangsa: International Journal of the Social Sciences, Education and Humanitis, 2026)
Chronic Energy Deficiency (KEK) in pregnant women is a condition of pregnant women due to an imbalance in energy and protein nutrient intake, so that the substances needed by the body are not met. There are two non-pharmacological efforts made in the prevention of KEK, namely by providing Oatbits Biscuits (Oat 8 Choco Hazel) and SGM Bunda Milk. To determine the effect of providing oatbits biscuits (Oat 8 Choco Hazel) and SGM Bunda milk on weight gain in pregnant women in the first trimester with KEK (Chronic Energy Deficiency) at PMB S in Bogor in 2024. Data collection used observation techniques by directly observing the objects to be studied which were then collected in a note. The results of this study on respondent I, the weight of the first visit was 40 kg with a LiLa of 21 cm (KEK), on the second visit the weight was 43 kg and on the third visit the weight was 45 kg and LiLa 22.5 cm (KEK). Respondent II's weight at the first visit was 50 kg and LiLa 22 cm (KEK), on the second visit the weight was 55 kg and on the third visit the weight was 56 kg and LiLa 24.5 cm (not KEK). Pregnant women in the first trimester with KEK who were given SGM Bunda milk intervention experienced faster weight gain compared to those given oatbits biscuits (Oat 8 Choco Hazel) intervention. For further studies, it is hoped that the frequency of consumption of oatbits biscuits (Oat 8 Choco Hazel) can be increased to two or three packs a day so that weight gain in pregnant women in the first trimester with KEK is greater and can reduce the incidence of pregnant women with KEK in Indonesia.